Strong and tough hydrogels crosslinked by multi‐functional polymer colloids. Issue 19 (25th September 2018) - Fu, Jun
ABSTRACT: Tough polymer hydrogels have great potential applications in soft actuators, artificial muscles, tissue engineering, and so forth. To improve the strength and toughness of hydrogels, numerous strategies have been developed to integrate efficient energy dissipation mechanisms into the hydrophilic networks. Among them, the use of macro‐crosslinkers to replace conventional chemical ones has become promising to develop tough hydrogels. Polymer colloids—including nano‐/microparticles, nano‐/microgels, hydrophobic associates, and block copolymer assemblies—have been employed in literature as multi‐functional macro‐crosslinkers that link polymer chains through covalent bonds or noncovalent interactions. The dislocation, deformation, desociation, and rupture of polymer colloids upon loadings are the major mechanisms to dissipate energy. This article provides a comprehensive account of most recent progresses on tough hydrogels crosslinked by polymer colloids, and explores the toughening mechanisms. It aims to inspire novel designs of tough hydrogels with multi‐functionalities. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1336–1350 Abstract : Multi‐functional polymer colloids including nano‐/micoparticles, microgels, micelles, and vesicles are widely used as macro‐crosslinkers to synthesize tough hydrogels by crosslinking hydrophilic polymer chains through covalent bonds, dynamic bonds, hydrophobic association, or supramolecular recognition. Upon loadings, the colloids dislocate, deform, or dissociate to dissipate energy and toughen the hydrogels. Some energy dissipation mechanisms are discussed in detail. This article aims to inspire novel design and synthesis of tough and functional hydrogels for applications in smart devices.